Adipose tissue metabolism in the postprandial period: microdialysis and arteriovenous techniques compared. - Summers, L; Arner, P; Ilic, V; Clark, M; Humphreys, S; Frayn, K (1998)
We investigated whether two different methods of studying metabolism in adipose tissue, microdialysis and the arteriovenous technique, produced comparable results during the postprandial period. Interstitial glycerol concentrations measured by microdialysis are usually used as an index of intracellular lipolysis, and it is not known whether they also reflect the intravascular action of lipoprotein lipase in the postprandial period. The two techniques were compared in 10 healthy subjects fed mixed meals. Interstitial glycerol concentrations reflected those measured in adipose tissue venous plasma. However, the calculation of the rate of glycerol release from adipose tissue using the microdialysis data differed systematically from that using arteriovenous difference measurement. The former method gave, on average, 40% lower values than the latter one. The difference is probably due to the assumptions that had to be made for the calculation of glycerol release. The two techniques have complementary places in the study of postprandial adipose tissue metabolism, with microdialysis reflecting intracellular hormone-sensitive lipase action rather than intravascular lipoprotein lipase.